Fake News Is Bad News Hoaxes, Half-truths and the Nature of Today's Journalism - Višňovský, Ján; Radošinská, Jana (IntechOpen, 2021)
We live in the era of the digital revolution characterized by easy access to obtaining, processing and disseminating information on a global scale. The emergence of these global digital spaces has transformed the world of communication. This shift in our understanding of what we should be informed about, when and how, manifests itself not only within mature liberal democracies, which grant their citizens and the media constitutionally guaranteed freedom of speech and rights associated with obtaining information, but also within developing countries with different types of political establishments. Moreover, many media producers, especially journalists and persons claiming to be journalists, abuse their crucial mission and, instead, foster a set of serious communication phenomena that threaten basic human rights and freedoms, weaken them or decelerate their development. The publication is focused on the ways fake news, disinformation, misinformation and hateful statements are spread across society, predominantly within the online environment. Its main ambition is to offer an interdisciplinary body of scholarly knowledge on fake news, disinformation and propaganda in relation to today's journalism, social development, political situation and cultural affairs happening all around the world.